2010
DOI: 10.3171/2009.6.jns081161
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus deep brain stimulator placement using high-field interventional magnetic resonance imaging and a skull-mounted aiming device: technique and application accuracy

Abstract: Object The authors discuss their method for placement of deep brain stimulation (DBS) electrodes using interventional MR (iMR) imaging and report on the accuracy of the technique, its initial clinical efficacy, and associated complications in a consecutive series of subthalamic nucleus (STN) DBS implants to treat Parkinson disease (PD). Methods A skull-mounted aiming device (Medtronic NexFrame) was used in conjunction with real-time MR imaging (Philips Intera 1.5T). Preoperative imaging, DBS implantation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
181
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(195 citation statements)
references
References 34 publications
11
181
0
3
Order By: Relevance
“…Our results (1.59 mm vector error) compare favorably with previously reported vector errors for intraoperative MRI (2.18 mm), 12 intraoperative imaging (O-arm) combined with frame-based stereotaxy (1.65 mm), 10 and conventional frame-based stereotaxy without intraoperative imaging (3 mm).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results (1.59 mm vector error) compare favorably with previously reported vector errors for intraoperative MRI (2.18 mm), 12 intraoperative imaging (O-arm) combined with frame-based stereotaxy (1.65 mm), 10 and conventional frame-based stereotaxy without intraoperative imaging (3 mm).…”
Section: Discussionsupporting
confidence: 79%
“…Starr et al previously reported on the correlation of the vector error and coronal approach angle, where the increased obliquity of the angle caused a higher positional error at the electrode tip. 12 A negative correlation was found between the distance of the electrode from the ventricle and both the vector error and trajectory deviation-in other words, both the vector error and the trajectory deviation were higher (less accuracy) when the electrode trajectory was closer to the ventricle. The strongest correlation was between the deviation error (radial displacement) and the distance from the ventricle in the range of 0-4 mm.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, this opened the way to the direct targeting technique. Indeed, the improvement of MRI sequences allowed to better delineate the shape of the STN and many groups started to describe direct targeting of the STN based solely on direct visualization of it [5,19,24]. As the coordinates of optimal target within the STN was reported by many groups, it appears that direct implantation of the lead based only on the anatomo-clinical definition of the target was a reasonable strategy, whereas some authors still used peri-operatory stimulation performed on the final lead (macro stimulation) to check the threshold of side effects.…”
Section: Rationale For Using Intra Op Mri Guidancementioning
confidence: 99%
“…Several attempts to improve the surgical technique have been described recently, leading to Bframeless^techniques [11] or to BMRI-verifiedB techniques [22][23][24]26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation